(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article is about the differences of allusive references and the precedent texts. The issues investigated are the notion of the pre-text, its types and the criteria of the pre-texts. Different types of references to the pre-texts are being analyzed. The conclusion is that in contemporary science the borders between different types of allusive references and precedent texts.